2011
DOI: 10.1007/s11434-011-4386-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sample width on flame spread over horizontal charring solid surfaces on a plateau

Abstract: Experiments were conducted on the Tibetan Plateau to investigate the effects of sample width (W) on flame spread over horizontal charring solid surfaces. The results show that the rate of spread is influenced by the combined effects of convection heat transfer and flame radiation. Moreover, two different regimes depending on sample width were found in flame spread behavior. The rate of spread decreased with width in the convective regime (W≤3 cm) but increased in the radiative regime (W>3 cm). Similar results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Previously, Zhang et al 18 have explored the variation of flame height with different sample widths in plateau. And Tsai 19 has done a series of experiments to find the power relationship between flame height and heat release rate for wall fires.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, Zhang et al 18 have explored the variation of flame height with different sample widths in plateau. And Tsai 19 has done a series of experiments to find the power relationship between flame height and heat release rate for wall fires.…”
Section: Resultsmentioning
confidence: 99%
“…the pool fire length of XPS is longer than EPS, which can be explained by the fact that the density of XPS is larger and then the melting liquid covers a larger area. Previously, Zhang et al 18 have explored the variation of flame height with different sample widths in plateau. And Tsai 19 has done a series of experiments to find the power relationship between flame height and heat release rate for wall fires.…”
Section: Characteristics Of Thermoplastic Pool Firementioning
confidence: 99%
“…This difference is explained by the higher pressure in Hefei, which leads to a greater burning rate, and thus a higher heat release rate per unit width. 15,16 As described by equation (3), the higher heat release rate per unit width causes a larger flame height.…”
Section: Surface Flame Heightmentioning
confidence: 99%
“…With the increase in sample width, the change in flame spread rate was not monotonic. Zhang et al 1,15 researched width effects on flame spread rate. They suggested that flame spread rate was influenced by flame heat feedback, which comprised two elements: convective heat transfer and radiative heat transfer.…”
Section: The Flame Spread Ratementioning
confidence: 99%
“…In addition to upward flame spread, some studies focused on the horizontal flame spread over combustible surfaces. A series of experiments were performed at different altitudes in to explore the impact of altitude and sample width on the flame spread characteristics. It was shown that the horizontal flame spread rate of whitewood and polystyrene first increases and then decreases with increasing sample width.…”
Section: Introductionmentioning
confidence: 99%